Seismic reliability assessment of slopes subjected to stochastic pulse-like ground motions - Wang, Ruohan; ICASP14; Beer, Michael; Chen, Guan; Dang, Chao (My University, 2023)
Near-fault pulse-like ground motions attract increasing attention in engineering because they tend to cause more severe damage to structures than ordinary ground motions. Landslides, as the most common natural hazard triggered by earthquakes, pose a critical threat to life and infrastructure safety. However, the seismic reliability assessment of slopes under near-fault pulse-like ground motions remains challenging due to the lack of records and the complexity of the dynamic response analysis. Hence, this study developed a framework for assessing the reliability of slopes under near-fault seismic excitation by integrating the pulse-like ground motion simulation method, the nonlinear dynamic analysis, and the extreme value distribution-based reliability method. A data-based empirical relationship between the design target spectrum in anti-seismic codes and seismic reliability was established for slopes, providing references for further study of seismic reliability in near-fault regions.
14th International Conference on Applications of Statistics and Probability in Civil Engineering(ICASP14)
PUBLISHED